Innovation on the Open Sea: Examining Competence Transfer and Open Innovation in the Design of Offshore Vessels - Borch, Odd Jarl; Solesvik, Marina (Talent First Network, 2015)
In this article, we discuss the role of open innovation in collaborative design processes in mature industries such as the shipping industry. We examine the design of high-tech offshore service vessels in environments characterized by high volatility and complexity. We elaborate on the role that accumulating and sharing core competences plays in speeding up the innovation process and increasing product value. We present a longitudinal case study of a shipping company implementing an open innovation approach that integrates its own core competences in offshore operations with the competences of ship designers and ship builders to develop a new design for challenging environments. In this article, we draw on an open innovation approach and a competence-based view to demonstrate how the firm can "reach out" to gain novel competences related to innovation, which may transform the competitive environment to the firm’s advantage. The article would be useful to innovation scholars and practitioners who work with innovative product development.